PELAKSAAN PEMBERIAN VAKSIN MASSAL DOSIS KEDUA DI KELURAHAN TLOGOMAS KOTA MALANG - Ika Cahyaningrum Ika; Supriyadi Supriyadi; Novita Dewi; Arie Jefri Ka’areyeno; Errick Endra Cita (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The government continues to strive for the availability of vaccines through multilateral and bilateral schemes to meet the current stock and maintain the vaccination rate in accordance with the existing vaccine stock (Widyawati, 2021). Tlagomas Urban Village, Lokwaru District, has a population of 19,826 (Central Bureau of Statistics Malang City, 2020). Of this population, not all of them have been vaccinated. So that the urban village government seeks accelerated vaccination programs, one of which is the implementation of a mass vaccine program. The purpose of this community service activity is to help implement the second dose of mass vaccine in Tlogomas Urban Village, Malang City. The methods used in this program are planning and preparation, implementation, and evaluation. The result of this activity is the availability of infrastructure and vaccine implementing officers as well as the implementation of the second mass vaccine activity in Tlogomas Urban Village, Malang City with a total number of 988 participants. The flow of vaccine activities includes registration, screening history and simple physical examination, administering vaccines and recording.